Implementasi Logika Fuzzy Untuk Menentukan Jumlah Produksi Roti Menggunakan Metode Tsukamoto - Ipung Dwi Antoni; Yulian Findawati (LPPM UBHINUS MALANG, 2024)
In an effort to improve the sustainability of the product manufacturing business, an appropriate strategy is needed to avoid losses due to wrong policies. This research proposes the application of Tsukamoto fuzzy logic as a solution to determine bread production based on inventory and demand. Bread, as a product with a short expiration period, requires smart production management to avoid waste and losses. Many bakeries still adopt the traditional way without considering fluctuations in market demand, which may result in overproduction or stock shortages. This research takes the case of Sarinda bakery, which is experiencing challenges in coping with market demand fluctuations. Through the use of the Tsukamoto fuzzy method, the results showed an accuracy rate of 93.06%, with a Mean Absolute Percentage Error (MAPE) of 6.94%, a very good category. This method proves its effectiveness in helping entrepreneurs determine the amount of bread production in accordance with changing market conditions, without the need to add many existing production facilities. The use of Tsukamoto fuzzy logic in this context can be a smart solution to improve bread production efficiency and optimize business profits.